Комунікативна спрямованість навчання діалогічного та монологічного мовлення у процесі підготовки студентів-філологів - Герасименко, Юлія Андріївна (Видавничий дім "Гельветика", 2022)
У статті обґрунтовано комунікативну спрямованість навчання діалогічного та монологічного мовлення у процесі підготовки студентів-філологів. Відповідно до впровадженого компетентнісного підходу, який реалізується в діалогічній та монологічній формах, визначено, що сьогодні важливу цінність має формування монологічного і діалогічного мовлення у студентів-філологів. Це пов’язано з тим, що діалогізація відображає природу дидактичної взаємодії, сприяє створенню сприятливих умов для здійснення діалогічного спілкування у системі відносин «науковопедагогічний працівник ‒ студент» на практичних заняттях з англійської мови, а монолог в процесі мовленнєвого спілкування знаходиться в постійній взаємодії з діалогом.
The article substantiates the communicative focus of teaching dialogic and monologic speech in the process of training philology students. According to the implemented competence approach, which is implemented in dialogic and monologic forms, it was determined that the formation of monologic and dialogic speech among philology students is of great value today. This is due to the fact that dialogization reflects the nature of didactic interaction, contributes to the creation of favorable conditions for the implementation of dialogic communication in the system of relations “scientific and pedagogical worker ‒ student” in practical English classes, and the monologue in the process of speech communication is in constant interaction with dialogue. In the process of analyzing this problem, the peculiarities of teaching monologic and dialogic speech of philology students in practical English classes were considered. In addition, various methods, exercises, techniques and technologies are described for the purpose of developing the communicative and speech skills of future philologists in the process of their performance of various forms of monologic and dialogic speech, which contributes to the formation of communicative, speech, professional skills and communication skills, and also promotes the expression of verbal means of communication, which activates the educational process and ensures mastery of lexical and grammatical material by philology students. The conclusions were drawn that the well-developed coherent speech of a philology student plays a significant role in the formation and development of personality, helps to think clearly and clearly in the process of speaking and easily establish contacts, maintain a conversation and communicate with people.
Keywords: комунікативна спрямованість; діалогічне мовлення; монологічне мовлення; інноваційні технології; комунікативний підхід; communicative orientation; dialogic speech; monologic speech; innovative technologies; communicative approach